NURSE INTENTION IN REPORTING PATIENT SAFETY INCIDENT - Supriyantoro; Krissadi, Lovi; Aida, Mus; Hanim, Wasifah (International Journal of Psychosocial Rehabilitation, 2020)
Data report on Patient Safety Incident in X Hospital Malang of the year 2018 showed that 64.83% occurred in the nursing unit, 18.5% in the pharmaceutical unit and 49.25% was conducted by the doctor while 7.40% took place in other units. The high rate of Patient Safety Incidents in the nursing unit is in accordance with the distribution of Patient Safety Incident Report published by KKPRS in 2011, where it is accounted for the highest incidence rate. Given the patient safety culture in X Hospital Malang is still inadequate, leading to the possibility of underreporting or hidden report. This study aimed to analyze the patient safety culture effect towards nurses’ desire in reporting Patient Safety Incident with the Perception of Standard Operating Procedures (SOPs) on the flow chart of Patient Safety Incident reporting as the intervening variable in X Hospital Malang. The research method was descriptive analysis with cross sectional quantitative approach (quantitative cross-sectional study). The primary data was collected by distributing questionnaires to nurses while Partial Least Square (PLS) was used as the analysis method, a structural equation analysis (SEM). The result of this study is considered quite well, from the total of 12 cultural dimensions, 7 are rated as poor, 1 is rated as average while the remaining 4 are rated as good. The perception of nurses towards the SOP on the flow chart of Patient Safety Incident Reporting is considered good, the understanding and the ability to distinguish Patient Safety Incident, creating reports, and performing grading are considered poor, although te understanding and the ability to identify incident are good. The desire of nurses in reporting Patient Safety Incident is rated as average even though the desire to report adverse and sentinel events is considered good, but the desire to report near miss and no harm events is poor. The result from this study conclude that patient safety culture has positive and significant impact on the perceptions of nurses towards sop on patient incident reporting flowchart. their perceptions positively and significantly affect their willingness to report patient safety incident. This study found that patient safety culture has positive and significant impact effect to their willingness to report patient safety incident through their perceptions towards sop on patient safety incident reporting flowchart